ENHANCING VOCATIONAL STUDENTS’ WORK READINESS THROUGH CURRICULUM MANAGEMENT AT SMK RADEN UMAR SAID KUDUS - Naila Shifwah; Masrukhin; Mohammad Dzofir (Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to describe the implementation of curriculum management to improve students’ work readiness at SMK Raden Umar Said Kudus. The main problem addressed is the high unemployment rate among vocational school graduates who are not yet fully work-ready. This research uses a qualitative approach with data collection techniques including interviews, observation, and documentation. The results show that the implementation of curriculum management encompasses planning, organizing, implementation, and evaluation stages. The school actively aligns its curriculum with industry needs through Project-Based Learning, Teaching Factory models, and partnerships with the Business and Industrial World (DUDI). The curriculum is designed thematically, integratively, and responsively to technological developments and the demands of the creative industry. Regular evaluations are conducted by both the school and industrial partners to ensure the achievement of student competencies. The conclusion of this study is that adaptive and industry-based curriculum management significantly enhances students’ work readiness and bridges the gap between education and employment sectors.